Engineering students’ engagement in entrepreneurship education - Christina Andin; Abdul Said Ambotang; Daniel Ugih; Syahrul Nizam Salam; Rosmiza M.Z. (Kalahari Journals, 2022)
Entrepreneurship education is one of the efforts for preparing graduates with the self-employed mindset. Accordingly, various entrepreneurial activities are implemented at the university level. One of the initiatives is to make entrepreneurship education compulsory for all university students. However, the study found that many graduates are not interested to become entrepreneurs and prefer to hunt for employment. Therefore, this study was conducted to explore the university students’ engagement while taking a compulsory entrepreneurship course. The case study involved 76 students majoring in engineering. The study was conducted using observation and documentation analysis methods. The results found that students were less engaged in implementing entrepreneurship learning activities. Most students failed to adhere to the due date of assignment submissions. Students were less interested in making marketing posts through social media and less critical thinking in solving their business problems. Overall, the achievement of business objectives was unsatisfactory. The students lack focus and limited time to engage actively in the learning activities. They have many commitments to other courses. The finding of this study can be used for deciding the best ways to promote an entrepreneurial mindset among university students.